Guidelines for seizure management in palliative care: proposal for an updated clinical practice model based on a systematic literature review - M. León Ruiz; M.L. Rodríguez Sarasa; L. Sanjuán Rodríguez; M.T. Pérez Nieves; F. Ibáñez Estéllez; S. Arce Arce; E. García-Albea Ristol; J. Benito-León (Neurología (English Edition), 2019)
Introduction: Very little has been written on seizure management in palliative care (PC). Given this situation, and considering the forthcoming setting up of the Palliative Care Unit at our neurorehabilitation centre, the Clínica San Vicente, we decided to establish a series of guidelines on the use of antiepileptic drugs (AEDs) for handling seizures in PC. Methods: We conducted a literature search in PubMed to identify articles, recent manuals, and clinical practice guidelines on seizure management in PC published by the most relevant scientific societies. Results: Clinical practice guidelines are essential to identify patients eligible for PC, manage seizures adequately, and avoid unnecessary distress to these patients and their families. Given the profile of these patients, we recommend choosing AEDs with a low interaction potential and which can be administered by the parenteral route, preferably intravenously. Diazepam and midazolam appear to be the most suitable AEDs during the acute phase whereas levetiracetam, valproic acid, and lacosamide are recommended for refractory cases and long-term treatment. Conclusions: These guidelines provide general recommendations that must be adapted to each particular clinical case. Nevertheless, we will require further well-designed randomised controlled clinical trials including large samples of patients eligible for PC to draft a consensus document recommending adequate, rational, and effective use of AEDs, based on a high level of evidence, in this highly complex area of medical care. Resumen: Introducción: Dada la escasez de directrices abordando este tema y con motivo de la futura creación de la Unidad de Cuidados Paliativos (CP) en nuestro centro de neurorrehabilitación, los miembros del equipo médico de la Clínica San Vicente hemos decidido proponer una serie de sugerencias sobre el empleo de fármacos antiepilépticos (FAEs) en el manejo de las crisis epilépticas (CEs) en CP. Métodos: Búsqueda de artículos en PubMed, últimos libros y recomendaciones de las guías de práctica clínica y sociedades científicas publicadas más relevantes, referentes al manejo de las CEs en CP. Resultados: La confección de este tipo de guías, además de identificar pacientes candidatos a recibir CP, es fundamental para garantizar un buen control sintomático de las CEs y evitar el sufrimiento innecesario de estos enfermos y sus familiares. Dadas las características de estos pacientes, se recomienda usar FAEs con presentación vía parenteral (preferiblemente intravenosa) y un perfil bajo de interacciones. Diazepam y/o midazolam serían los más idóneos para la fase aguda, y levetiracetam, ácido valproico y/o lacosamida para casos refractarios y/o como tratamiento crónico. Conclusiones: Estas recomendaciones deben considerarse una guía de abordaje integral, debiendo adaptarse a la idiosincrasia de cada caso clínico en particular. Sin embargo, se necesitan ensayos clínicos controlados, aleatorizados, bien diseñados, que incluyan muestras amplias de pacientes subsidiarios de CP, para redactar un documento de consenso que permita recomendar con un mayor nivel de evidencia y de forma generalizada, la utilización adecuada, racional y efectiva de FAEs en este ámbito médico-asistencial de elevada complejidad. Keywords: Cancer, Epileptic seizure, Palliative care, Epilepsy, Antiepileptic drug, Terminal illness, Palabras clave: Cáncer, Crisis epiléptica, Cuidados paliativos, Epilepsia, Fármaco antiepiléptico, Situación de enfermedad terminal